Frailty assessment in older urological patients prior to surgery: a systematic review and narrative synthesis. (May 2020) - Haren, Andrea; Lal, Rajni; Walker, David; Nair, Rajesh; Partridge, Judith; Dhesi, Jugdeep
Background: Radical cystectomy (RC) and urinary diversion are the recommended treatment for patients with muscle invasive bladder cancer. This is complex surgery, associated with significant patient morbidity and mortality. Frailty has been shown to be an independent risk factor for adverse outcomes in several surgical populations. Preoperative assessment of frailty is advocated in current guidelines but is not yet standard clinical practice. Aims: This systematic review and narrative synthesis aims to examine whether patients undergoing RC are assessed for frailty, what tools are used, and whether an association is found between frailty and adverse outcomes in this population. Results: Nine studies, published within the last 4 years, describe the use of tools reporting to measure frailty in the RC population. All demonstrate increased risk of adverse postoperative outcomes with higher frailty levels. Only one study used a validated frailty tool. The majority of studies measure frailty using variations on a tool derived from a large database (ACS-NSQIP) effectively counting co-morbidities, rather than assessing the multidomain nature of the frailty syndrome. Conclusion: The recognition of frailty as an important consideration in the perioperative period is welcome. This systematic review and narrative synthesis demonstrates the need for collaboration in research and delivery of clinical care for older surgical patients. Such collaboration may provide clarity regarding terms such as frailty and multimorbidity, preventing the development of assessment tools inaccurately measuring these discreet syndromes interchangeably. More accurate assessment of patients in terms of frailty, multimorbidity and functional status may allow better modification and shared decision making leading to improved postoperative outcomes in older patients undergoing RC.